Marketing Strategy Analysis Using Business Model Canvas and SWOT Matrix (A Case Study at Queen Laundry Bogor) - Hendarsih, Ida; Estiani, Tri Indah; Martanti, Amas Sari (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The aim of the research is to develop a marketing strategy that can be implemented for Queen Laundry Bogor MSMEs. By using the Business Model Canvas approach as an analytical tool and then from the results of the analysis findings, it is continued with internal and external analysis of the company to obtain more comprehensive results, namely SWOT matrix analysis, Quantitative Strategic Planning Matrix (QSPM), this research is descriptive research that describes and analyzing data obtained during research with a qualitative approach. The results of the analysis show that the business model used by UMKM Queen Laundry Bogor has not fully utilized technological advances for marketing. After being given direction in the marketing strategy, a decision was obtained from the business owner with the target of consumers serving the market share of all segments using alternative strategies obtained to improve laundry facilities, improve product quality and service to attract consumers, improve management capabilities and cooperation for company goals. providing special packages or services, and maintaining good relationships with suppliers or areas around the laundry. The recommended priority marketing strategy is to maintain the company's image, providing services to promote pick-up and drop-off services.